WASTEWATER QUALITY AND POLLUTION LOAD OF EACH STAGE IN TEMPEH PRODUCTION - Vita Pramaningsih; Hansen Hansen; Sarva Mangala Praveena; Ucik Ika Fenti Styana (Universitas Trisakti, 2022)
Aim: This study is purpose to understand the chemical and physical characteristics and pollution load in each step of tempeh wastewater: washing, boiling, soaking and mixing. Tempeh is traditional food from soybean fermentation. Tempeh has a lot of healthy contents as protein and vitamin. However, wastewater from tempeh production is discharge to river directly which considered as environmentally damaging. However, the characteristics of wastewater from tempeh production and its level of environmental impacts to environment are limitedly studied. Methodology and Results: Tempeh wastewater was analyzed in chemical and physical parameters. Chemical characteristics analyzed are pH, Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD). pH was measured using pH meter, BOD using SNI 6989.72:2009 method and COD using SNI 6989.2:2019 method. The physical parameter analyzed is Total Suspended Solid (TSS) and analyzed using SNI 6989.3: 2019 method. Pollution load calculated by deviation maximum pollution load and pollution load existing. Result of this study findings indicated that the highest BOD 299.40 mg/L and COD 540.66 mg/L was found in soaking step compared to other steps in tempeh production. Highest TSS 655.20 mg/L was found in boiling step. The pH values in all steps were acidic 4 and 5. Allocation Pollution load of: TSS overall exceeded the capacity, BOD and COD overall exceeded the capacity except in washing step (BOD 304.39 kg/day and COD 857.78 kg/day). Conclusion, significance and impact of study: The Highest TSS of tempeh wastewater processes was in boiling step while the highest organic matter was detected in soaking. Further for whole pH were acidic and exceeded the standard. Allocation of pollution load for TSS, BOD and COD exceed the standard except for BOD and COD in washing waste. Overall tempeh wastewater needs treatment to prevent river pollution.